O envolvimento familiar na educação da criança com transtorno do espectro autista. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Using a qualitative approach, theresearch explores familyideasandbehaviors in relationto inclusive education. Data wascollectedthroughquestionnaireson Google Formsandtreatedwiththe help ofcontentanalysis. The categorieslisted in thisstudyfocusontwomaindiscussions: 1. familysupportandthechallengesfaced in theeducationalprocessofchildrenwith ASD; 2. familysupportandthefacilitatingaspectsoftheeducationalprocessofchildrenwith ASD. The studyadoptsanemic perspective, valuingfamilyexperienceswithoutdefining standards ofconductadopted, butlookingatwhat emerges fromthe data. hefamilymemberswhotookpart in thisstudylistdifficultiesthatintersectwiththeschool, such as thelowqualityof training for educationprofessionals in the inclusive perspective, especiallywhen it comes todealingwiththespecificneedsofchildrenwith ASD. The involvementofparents in theirchildren'seducational path goesbeyondschoollines, notingthatthereis, in all cases, privateinvestment in otherservices in theclinicalandpedagogicalareas. The familynarratives show a dailystruggle for inclusive educationand a constantsearch for strategiestopromotetheirchildren'sdevelopment. Thisjourney includes understandingdiversity, theirchildren'swaysof learning andfacingtheemotionaland social challengesassociatedwithcaring for a childwith ASD. Creating a truly inclusive environment requires the joint effortofallthoseinvolved in theeducationalprocess, as well as a closer look atthespecificdemandsofchildrenwith ASD andtheirfamilies.
Keywords: Transtorno do Espectro Autista; Família; Escola; CNPQ:: CIÊNCIAS HUMANAS